New record of Orgalonia van Achterberg and description of a new species of Orgilus Haliday (Hymenoptera: Braconidae: Orgilinae) from India - Ahmed, Ishtiaq; Kazmi, Sarfrazul Islam; Rameshkumar, Anandhan (Zootaxa, 2022)
Orgilinae is a small group of family Braconidae containing about 200 species globally including 4 Indian species. In the present work genus Orgilonia is recorded for the first time from India along with the redescription and illustrations of Orgilonia ashmeadi (Viereck, 1911). A new species Orgilus indicus sp. nov. is described from India, and a key to Indian tribes, genera and species with a checklist of Indian species belonging to subfamily Orgilinae is also provided.